Inflation Targeting: Eliminating Economic Growth and Structural Deformation in Russia - О. S. Sukharev; E. N. Voronchikhina (Финансы: теория и практика)
The paper examines the impact of the inflation targeting policy as a basic component of the government’s general anti-inflationary measures on economic growth and the structure of the Russian economy. The purpose of the study is to identify the impact of targeting policy in Russia on the rate of economic growth and the structure of the economy, represented by aggregated sectors — manufacturing and transactional raw materials. The research methodology consists of empirical-statistical structural, index methods of analysis, econometric modeling, reduced to the construction of factor models by type of production functions. Taking into account these methods, an algorithm has been developed to assess the impact of price dynamics and its targeting on macroeconomic dynamics and structure of the economy. Following this algorithm allowed, on the one hand, to give measurable estimates of the impact of consumer and industrial prices on general inflation in the country, and of inflation itself on GDP dynamics, on the other hand, to determine the degree of deformation of the structure of the Russian economy under the influence of inflation targeting policy. The main result of the study is that the large role of the transactional raw material sector in generating inflation and the fact that the introduction of targeting as a method of inflation suppression policy fixes the structure of the economy, slowing down development, which also affects growth towards its slowdown, is confirmed. Thus, a moderately restrictive monetary policy slows down growth and deforms the economic structure. The prospect of applying the results is that a change in inflation targeting policy, as well as an approach that assesses the impact of price dynamics on economic growth and its structure, which should lead to the justification of flexible ranges of inflation targets and the targeting of nominal GDP as a policy goal, taking into account the necessary change in the sectoral economic structure. In theoretical terms, future research on the adsorption of the money supply by the economic structure and determining the impact of such absorption on price dynamics is important.